Chinese SLE Treatment and Research group (CSTAR) registry VII: prevalence and clinical significance of serositis in Chinese patients with systemic lupus erythematosus. (May 2016) - Zhao, J; Bai, W; Zhu, P; Zhang, X; Liu, S; Wu, L; Ma, L; Bi, L; Zuo, X; Sun, L; Huang, C; Tian, X; et al.
Objectives: To investigate both the prevalence and clinical characteristics of serositis in Chinese patients with systemic lupus erythematosus (SLE) in a large cohort in the Chinese SLE Treatment and Research group (CSTAR) database. Methods: A prospective cross-sectional study of patients with SLE was conducted based on the data from the CSTAR registry. Serositis was defined according to the 1999 revised American College of Rheumatology (ACR) criteria for SLE – that is, pleuritis/pleural effusion and/or pericarditis/pericardial effusion detected by echocardiography, chest X-ray or chest computerized tomography (CT) scan. Peritonitis/peritoneal effusion were confirmed by abdominal ultrasonography. We analysed the prevalence and clinical associations of serositis with demographic data, organ involvements, laboratory findings and SLE disease activity. Results: Of 2104 patients with SLE, 345 were diagnosed with serositis. The prevalence of lupus nephritis (LN), interstitial lung disease and pulmonary arterial hypertension, as well as the presence of leukocytopenia, thrombocytopenia, hypocomplementemia and anti-dsDNA antibodies was significantly higher in patients with serositis ( P  < 0.05). Significantly higher SLE disease activity scores were found in patients with serositis compared to those patients without serositis ( P  < 0.05). Lupus-related peritonitis had similar clinical manifestations and laboratory profiles as serositis caused by SLE. Conclusions: There is a significant association of nephropathy, interstitial lung disease, pulmonary arterial hypertension, hypocomplementemia, leukocytopenia, thrombocytopenia and elevated anti-dsDNA antibodies with serositis. The results suggest that higher SLE disease activity contributes to serositis development, and should be treated aggressively.